Cooperative interactions between the interleukin 2 receptor alpha and beta chains alter the interleukin 2-binding affinity of the receptor subunits. - Roessler, E (1994)
The interleukin 2 (IL-2) receptor (IL-2R) is a multisubunit receptor that includes three major IL-2 binding subunits, the IL-2R alpha, beta, and gamma chains. We have detected and analyzed cooperative interactions between the IL-2R alpha and beta chains (IL-2R alpha and IL-2R beta, respectively) in COS cells transfected with cDNAs encoding the IL-2R alpha, the IL-2R beta, or both cDNAs. We demonstrated that IL-2 F42A, an analog that fails to bind to the isolated IL-2R alpha subunit and would be predicted by the hierarchical affinity-conversion model to have impaired binding to cells expressing both chains, instead readily binds to the IL-2R alpha/beta heterodimer in COS cells. Furthermore, this binding is abolished by the antibody HIEI that separates the two IL-2R subunits. The monoclonal antibodies anti-Tac and Mik-beta 1 directed at the IL-2-binding sites on IL-2R alpha and IL-2R beta, respectively, block ligand binding to the heterodimer. This binding pattern is inconsistent with the strict hierarchical affinity-conversion model that mandates an initial binding of IL-2 to IL-2R alpha followed by binding of the IL-2/IL-2R alpha complex to IL-2R beta. Instead, our results support an alternative model of preformed complexes of IL-2R beta with other IL-2R subunits. In this alternative model, IL-2R alpha and -beta exist in part as preformed complexes in which the affinity of IL-2R beta for IL-2 is altered by the proximity of IL-2R alpha, through mechanisms that do not require the prior binding of IL-2 to IL-2R alpha.